Unveiling Academic-Cultural Identities: A Semiotic Analysis of Student Article Titles - Deri Fikri Fauzi; Susi Yuliawati (ICoLLiTec (International Conference on Literature Linguistics and Teaching), 2025)
This study explores the intricate role of student research article titles as semiotic constructs that encapsulate academic and cultural identities within academic writing. These titles, though concise, are complex sites of meaning-making that pose challenges in understanding their full significance, particularly in non-Western academic contexts. The complexity of these titles as reflections of identity presents an analytical hurdle in qualitative research. To address this, the study employs a qualitative semiotic analysis, guided by the research question: “How do semiotic signs in student research article titles reflect academic and cultural identities?” Drawing on Saussure’s signifier-signified framework and Peirce’s triadic model (icons, indices, symbols), this analysis examines 13 titles from a Writing for Academic Contexts course, categorizing them by themes (e.g., media, literature, social issues, language) and analyzing their linguistic and theoretical structures. The unstructured yet rich nature of these titles mirrors the multifaceted identities they represent. This paper proposes an analytical approach, adaptable to methodologies like discourse analysis or case studies, grounded in a critical realist philosophy to uncover deeper insights into identity construction. It illustrates how students weave local (e.g., Gadis Kretek) and global (e.g., digital media) references alongside formal academic structures to negotiate personal and scholarly identities, offering pedagogical implications for enhancing intercultural competence in academic writing..